Pemodelan Tekanan Bawah Permukaan Dengan Menggunakan Metode Time Series Dalam Proses Injeksi Slurry di Sumur Disposal Duri Field - Bambang Sutrimo (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2021)
Oily sand and water contaminated with oil is part of the results of exploration and exploitation of petroleum categorized as hazardous and toxic waste (B3), it is necessary to carry out special processing into slurry fluid and injection into disposal wells. The main problem in the injection process is the increase in bottom hole pressure during the injection process which causes well plugging problems and hampers oil production activities in the Duri field. The main objective of this research is to determine the best model and safety factor in the injection process using the time series Arima Software ‘R’ method with the parameters of the slurry flow rate and slurry composition based on the injection strategy at injection well B. Forecasting Arima in well B with an injection flow rate of 2,3 m3/minute and a slurry concentration of 25% waste and 75% water is Arima model 3 (1,1,0) with the smallest value of Akaike Information Criteria (AIC) 2,773,98 and the smallest Schwarzt Bayesian Information Criteria (SBC) is 2,781, the average bottom hole pressure predicted is 1,256.4 psi and the average bottom hole pressure from the field data is 1,247.54 psi. Validation of the forecasting model for well B that the percentage of model error compared to field data in well B is 0.37%, Root Mean Square Error (RMSE) 4,85 and model error using pressure gradient 0,37%. Arima modeling can be applied to predict bottom hole pressure based on the injection strategy in the injection process to the disposal well.